Dinamika Transnational Advocacy Networks: Diaspora Tionghoa dalam Negosiasi Budaya dan Identitas di Indonesia Pasca-Orde Baru (1998-2008) - Jasmine Nuzulul Ramadhanty (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2026)
The Chinese diaspora in Indonesia is one of the ethnic groups that experienced systemic marginalization during the New Order and faces structural challenges in articulating cultural identity and obtaining equal citizenship recognition. The 1998 reforms opened up new political opportunities, but did not necessarily erase the legacy of discrimination. This study analyzes how the transnational networks of the Chinese diaspora used the strategy of Transnational Advocacy Networks (TANs) to shift their position from exclusion to social acceptance in the period 1998–2008. By elaborating on the theory of TANs from Keck & Sikkink (1998) to its development by Evans & Rodríguez-Garavito (2018), this study highlights three main variables; Boomerang Pattern, Political Entrepreneurs, and Growth of International Contact, which are used by the diaspora in building cross-border advocacy networks. Furthermore, this study emphasizes the importance of institutional transformation from the bottom up as a form of sustainable social change. The findings show that diaspora networks are not only pressuring the state to change discriminatory policies, but also reshaping national discourse through symbolic, cultural, and collaborative strategies. This study concludes that the Chinese diaspora is an important actor in the democratization of Indonesian culture through adaptive and contextual transnational advocacy networks.